2020
DOI: 10.1029/2020jc016113
|View full text |Cite
|
Sign up to set email alerts
|

Control of the Oceanic Heat Content of the Getz‐Dotson Trough, Antarctica, by the Amundsen Sea Low

Abstract: The changing supply of warm Circumpolar Deep Water (CDW) to the West Antarctic continental shelf is responsible for the basal melting and thinning of the West Antarctic ice shelves that has occurred in recent decades. Here we assess the variability in CDW supply, and its drivers, from a multiyear mooring deployed in, and a regional ocean model spanning, the Getz‐Dotson Trough, Amundsen Sea. Between 2010 to 2015, the CDW within the trough underwent a pronounced cooling and freshening, associated with changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
37
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 66 publications
9
37
1
Order By: Relevance
“…In addition to continental changes, a stronger ASL is also associated with reduced sea-ice cover in the Bellingshausen/Amundsen Sea sector and a sea-ice cover expansion in the Ross Sea sector (e.g., Raphael and Hobbs, 2014). A deeper ASL also drives oceanic changes, enhancing warm ocean water upwelling towards ice shelves, inducing basal melting (e.g., Mankoff et al, 2012;Dotto et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to continental changes, a stronger ASL is also associated with reduced sea-ice cover in the Bellingshausen/Amundsen Sea sector and a sea-ice cover expansion in the Ross Sea sector (e.g., Raphael and Hobbs, 2014). A deeper ASL also drives oceanic changes, enhancing warm ocean water upwelling towards ice shelves, inducing basal melting (e.g., Mankoff et al, 2012;Dotto et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…We therefore identify an interesting new mechanism in which the interannual variability of mCDW in front of DIS previously revealed by Jenkins et al (2018) could be explained by the variability of Ekman pumping de- rived from local atmospheric circulation in DGT, seasonally modulated by the movements of the sea ice edge. This is complementary to theories that relate heat content variability to anomalous heat advection at the continental shelf break driven by changes in shelf break undercurrent amplitude and winds (Carvajal et al, 2013;Dotto et al, 2020;Kim et al, 2017;Thoma et al, 2008;Wåhlin et al, 2013). Since both shelf break winds and continental shelf winds share similar variability and drivers, further investigation is needed to detail the relative role of each in dictating the interannual variability of mCDW in front of DIS.…”
Section: Discussionmentioning
confidence: 80%
“…Many scholars have investigated the variability and mechanism of mCDW flowing into the DGT based on field observations (e.g., Dotto et al, 2020;Kim et al, 2017;Wåhlin et al, 2012Wåhlin et al, , 2013. Wåhlin et al (2012) argued that the intrusion of warm and salty water over the continental slope may be due to upslope transport in the bottom Ekman layer.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The driving mechanism behind seasonality of the heat transport into the DIS cavity is interpreted to be caused by local OSSC, induced by changes in sea ice and wind distribution, in turn linked to changes of the polynya area and sea ice distribution 40 . Previous studies have shown that the wind field and atmospheric circulation affects not only the seawater circulation at the ice shelf front but also the variability of warm water flowing into the DGT near the center of the continental shelf 10 , 11 , 23 , 41 . Also, local wind forcing in front of PIG has been attributed a significant modulator for the short-term (less than one month) variability of the upper thermocline depth and basal melting there 42 .…”
Section: Discussionmentioning
confidence: 99%